(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
The concept of integration in elementary mathematics education is pivotal, serving as a foundation for more complex mathematical thinking and problem-solving. This article delves into the essence of integration, exploring its theoretical underpinning and methodological significance. By examining its role in mathematics pedagogy, we propose a structured approach to enhancing students’ understanding and application of integration, drawing on prior research and contemporary educational practices